IMRP-LAN design of a teleoperated indoor mobile robot system with environment mapping capabilities - Quevedo, Gene Paul L. (2007)
Indoor mobile robots employ localization and mapping techniques for navigation of their environment, but this requires substantial amount of processing power. Localization and mapping are both fundamental tasks performed by indoor mobile robots today. This project aims to design a client-server, wireless network link from a desktop to the indoor mobile robot. The server will be a desktop PC loaded with a program that will establish a network link to the indoor mobile robot. The program will retrieve data from the robot's sensors and then process the data for localization and mapping. The PC server will then relay commands to the indoor robot to complete the localization and mapping process. The indoor mobile robot will link to the server using EZ80Acclaim! Development kit connected to a WiFi router, which in turn connects to the local area network of a specific indoor environment.